The level of trait emotional intelligence among final year students in Universiti Teknologi Malaysia [electronic resource] - Nadiah Nadzirah Rashid, 1992-, author (2014)
Project Paper (Sarjana Muda Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2014